Output polarization characteristics of a GaN microcavity diode polariton laser - Bhattacharya, Aniruddha (2017)
We report the steady state output polarization characteristics of GaN-based microcavity polariton lasers operated with electrical injection at room temperature. The output is unpolarized below the nonlinear threshold injection current and is linearly polarized above it with a maximum degree of polarization of ∼ 22 % . The results have been analyzed theoretically, and the calculated results are in agreement with the measured data. We have also measured the polarization-resolved output light current characteristics, wherein a distinct lowering of the non-linear threshold is observed in one device. This is interpreted in terms of spatially inhomogeneous lifting of degeneracy and polarization splitting in the microcavity.